Copper hexacyanoferrate–polymer composite beads for cesium ion removal: Synthesis, characterization, sorption, and kinetic studies. Issue 1 (4th November 2012) - Dwivedi, Charu; Kumar, Amar; Singh, Krishan Kant; Juby, Ajish K.; Kumar, Manmohan; Wattal, Piaray Kishen; Bajaj, Parma Nand
Abstract A novel synthetic method for the preparation of different sorbent–polymer composite beads has been developed under simple laboratory conditions. Copper hexacyanoferrate was synthesized, and its composite beads of required size were synthesized by phase‐inversion technique, using polyethersulfone as the polymer matrix. Suitable size and mechanical stability, along with their spherical shape, make these composite beads most appropriate for column operation. The efficiency of these composite beads was tested for the removal of cesium, using radioanalytical techniques, in batch conditions. The effect of pH, the initial metal ion concentration, and contact time was also investigated. The synthesized beads perform best in the pH range 5–9. Different sorption isotherm models were applied to the experimental data. Equilibrium data are represented well by the Langmuir isotherm equation, with a monolayer sorption capacity of 1.56 mg g−1 for the swollen beads. Kinetic modeling analysis, by fitting the data in the pseudo first‐order, pseudo second‐order, and intraparticle diffusion equations, shows that the pseudo second‐order equation is the most appropriate model for the description of sorption of cesium ions onto the composite beads. The process mechanism is found to be complex, consisting of both intraparticle diffusion and film diffusion. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013